An on-ice aerobic maximal multistage shuttle skate test for elite adolescent hockey players - Leone, M.; Leger, L. A.; Lariviere, G.; Comtois, A. S. (International Journal of Sports Medicine, 2007)
The aim of this study was to design an on-ice test to predict V·O2max in ice hockey players. 30 elite hockey players (age 14.7 ± 1.5 years) participated in this study. The oxygen uptake was assessed at submaximal and maximal velocities during an on-ice intermittent maximal multistage shuttle skate test with a 1-min/0.5-min work/rest ratio. The procedure consisted of skating back and forth on a distance of 45 m (stop and go) while following a pace fixed by an audible signal: initial velocity of 3.5 m · s-1 with increments of 0.2 m · s-1 every stage. The skating multistage aerobic test (SMAT) enabled the prediction of the V·O2max (ml · kg-1 · min-1) from the maximal velocity (m · s-1) by means of the following regression equation: V·O2max = 18.07 × (maximal velocity) - 35.596 (r = 0.97, SEE = 3.01). The test-retest correlation was 0.92 and SEE = 0.56 stage (n = 23). Following the SMAT validation, an additional group of 112 elite male (age = 14.2 ± 1.3 years) and 31 elite female (age = 14.0 ± 1.2 years) ice hockey players performed both the 20-m shuttle run test and the SMAT, which was more specific and accurate to predict V·O2max. The overall results suggest that the SMAT is highly specific, valid and reliable for the prediction of V·O2max of ice hockey players.